2014
DOI: 10.11646/zootaxa.3755.5.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of insular Rock Gecko (Genus Cnemaspis Strauch, 1887) from the Bidong Archipelago, Terengganu, Peninsular Malaysia

Abstract: A new insular species Cnemaspis bidongensis sp. nov. (Squamata: Gekkonidae), is described from Pulau Bidong, Terengganu, Peninsular Malaysia and bears a unique suite of morphological and color pattern characters that differentiate it from all other congeners. Cnemaspis bidongensis sp. nov. is the sister species to C. kendallii (Gray) and represents the fifth insular endemic species of Cnemaspis on archipelagos along the east coast of Peninsular Malaysia. This species survived massive deforestation of the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However the endemic gecko, Cnemaspis bidongensis, did not seem affected. Grismer et al (2014) inferred that C. bidongensis, unlike most of its congeners, is not a microhabitat specialist. This could have helped its survival undeterred by the island's severely degraded ecosystem in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the endemic gecko, Cnemaspis bidongensis, did not seem affected. Grismer et al (2014) inferred that C. bidongensis, unlike most of its congeners, is not a microhabitat specialist. This could have helped its survival undeterred by the island's severely degraded ecosystem in the past.…”
Section: Discussionmentioning
confidence: 99%
“…However, other terrestrial fauna was not reported until recently. Roslan et al (2016) surveyed the island's bat fauna, Fathihi-Hakimi et al (2017) studied the butterfly diversity, and Grismer et al (2014) described a new species of lizard, Cnemaspis bidongensis. Zakaria et al (2017) followed up with an inventory of the island's herpetofaunal diversity in which 12 species of lizards were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases this may result in species descriptions with many authors. For instance, several gecko species have been described with more than a dozen authors, such as Cyrtodactylus phuocbinhensis (Nguyen et al 2013), Cyrtodactylus taynguyenensis Nguyen et al 2013, Cyrtodactylus puhuensis (Nguyen et al 2014, and Cnemaspis bidongensis (Grismer et al 2014), each with 14 authors. None of these approach the reptile species with the highest number of authors though, which is the leiosaurid Enyalius capetinga Breitman et al 2018, with 27 authors.…”
Section: A History Of Gecko Discoverymentioning
confidence: 99%
“…In comparison to the lizards, freshwater turtles and, tortoises groups, ecological and taxonomical study solely focusing on snakes in Terengganu is non-existed (Grismer and Chan 2008;Grismer et al 2009;2014a;Chan and Norhayati 2010;Chan and Chen 2011;Shahirah-Ibrahim et al 2018).…”
Section: Introductionmentioning
confidence: 99%